A Risk-Based Approach to Assess the Effectiveness of Sprinklers in Buildings with Combustible Cladding - Kjetil Pedersen; Kate Nguyen; Ashley Hunt (Fire)
This study investigates a risk-based approach to evaluate the effectiveness of sprinklers in residential buildings to offset the risk premium imposed by combustible cladding (expanded polystyrene and aluminium composite panels) installed on such buildings in Victoria, Australia. This approach builds upon the Initial Fire Spread in Cladding Assessment Number (IF-SCAN), a concept pioneered by Cladding Safety Victoria as a triage tool in their rectification program. The analysis uses published data from real fires in buildings with and without sprinkler systems installed. It considers three criteria: death rates, injury rates, and construction cost. The construction cost was determined using an existing costing model currently employed in Victoria. The results of this study suggest a higher risk tolerance can be accepted for combustible cladding on buildings equipped with sprinkler systems over that set out in government policy. More specifically, it was found that a building fully protected by sprinklers can generally counterbalance the fire risk posed by combustible cladding spanning up to seven apartments, while a span of up to ten apartments could be considered for buildings without balconies or a private courtyard.